The organization of the dental service in the Voronezh region - Yuri E Antonenkov (Journal of Dental Problems and Solutions - Peertechz Publications, 2021)
Introduction: The article «Organization of dental services in the Voronezh region» - a large subject of the Russian Federation (RF), the features of the organization of dental care for adults and children are considered.  Materials and methods: Analytical methods and extracts of data from reports of medical organizations of the dental profile of the Voronezh Region for 2017-2019 were used. In accordance with the action plan of the Department of Health of the Voronezh Region, the issues of primary prevention of dental diseases among the population of the Voronezh Region are covered within the framework of the state program of the Russian Federation «Development of Health Care». When considering. Results: The current state of science and practical health care to preserve the health of the population is reflected, and at the same time, the relevance of dental research remains unchanged. The working dental organizations of the region are described. The analysis of literature sources and reporting materials showed the importance of dynamic observation of medical and social indicators, conditions and lifestyle, the level and structure of dental morbidity, and the demographic situation. The author of the work is well aware of the importance of the background of dental measures aimed at prevention (first of all) and treatment (if necessary). Speaking about the indicators of morbidity in dentistry, the author emphasizes the need to study it to assess the public health of the entire population. Conclusion: It is emphasized that the priority directions of the development of the dental service of the Voronezh region can be considered (including recommended to other regions): strict implementation of the Program of State Guarantees to the population of the region, equipping dental departments and offices in accordance with the standards of equipment, improving the availability, safety and quality of dental care to the population, as well as the priority of prevention in the field of health protection, including through the school dental service.